2014
DOI: 10.1016/j.juro.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Biomarker Profiles in Urinary Sediments and Exosomes

Abstract: Exosomes have characteristics that enable them to serve as a stable substrate for biomarker analysis. Thus, digital rectal examination enhances the analytical performance of biomarker analysis in exosomes and cell pellets. The diagnostic performance of biomarkers in exosomes differs from that of cell pellets. Clinical usefulness must be prospectively assessed in larger clinical cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
1
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 20 publications
(21 reference statements)
4
72
1
3
Order By: Relevance
“…Arroyo et al [11], using differential centrifugation and size-exclusion chromatography to characterize circulating miRNA complexes in human plasma and serum, concluded that the vesicle associated miRNAs represents the minority, whereas around 90% of miRNAs in the circulation is present in a non-membrane-bound form. Additionally, Dijkstra et al [12] compared PCA3 and TMPRSS2-ERG expression levels in urinary sediments and exosomes and concluded that in exosomes these biomarkers had lower analytical sensitivity, although exosomes seem to be a more robust source of urinary biomarker. On the other hand, according to Gallo et al [13] exosome isolation improves the sensitivity of miRNA from human biological fluids, including serum and saliva.…”
Section: Biogenesis and Function Of Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Arroyo et al [11], using differential centrifugation and size-exclusion chromatography to characterize circulating miRNA complexes in human plasma and serum, concluded that the vesicle associated miRNAs represents the minority, whereas around 90% of miRNAs in the circulation is present in a non-membrane-bound form. Additionally, Dijkstra et al [12] compared PCA3 and TMPRSS2-ERG expression levels in urinary sediments and exosomes and concluded that in exosomes these biomarkers had lower analytical sensitivity, although exosomes seem to be a more robust source of urinary biomarker. On the other hand, according to Gallo et al [13] exosome isolation improves the sensitivity of miRNA from human biological fluids, including serum and saliva.…”
Section: Biogenesis and Function Of Mirnasmentioning
confidence: 99%
“…According to Cheng et al [14], miRNAs were found to be significantly enriched and intact in urine-derived exosomes compared with cell-free urine. In fact, exosomes have been found as a robust source of urinary biomarkers, showing the presence after digital rectal examination of high levels of PCA3 and TMPRSS2-ERG in urinary exosomes [12]. However, no studies are currently available about miRNAs in urinary exosomes in PCa, even when they have been widely explored in benign nephropathies [119,120].…”
Section: Mirnas In Urine In Prostate Cancermentioning
confidence: 99%
“…Prostate fluid constitutively leaks into urine and prostate massage (usually as a consequence of digital rectal examination) before urine collection increases the amount of prostasomes in urine (37,(67)(68)(69). The presence of prostasomes in EV fractions isolated from urine was confirmed by detection of prostate-specific proteins, including prostate-specific membrane antigen (PSMA), prostatic acid phosphatase, and prostate transglutaminase (67,(70)(71)(72)(73).…”
Section: Prostasome-associated Pca Protein Markers In Urinementioning
confidence: 99%
“…Немалое значение исследование микроРНК может приобрести в отношении оценки прогноза новообра-зований гормонозависимых тканей [72]. Наконец, важным элементом прикладного рассмотрения данной проблемы представляется оценка профиля экспрессии микроРНК с диагностической целью в биопсийном материале, а также в циркуляции (крови или моче), т. е. в составе экзосом, у больных РПЖ и РМЖ [73,74], что может оказаться полезным для раннего разграни-чения гормоночувствительных и гормонорезистент-ных случаев этих заболеваний. Нельзя исключить и перспективность уже частично апробированной модификации гормоночувствительности и гормоно-резистентности опухолевой ткани под влиянием ан-тидиабетического бигуанида метформина, что может реализоваться и путем вовлечения микроРНК и ассо-циированных с ними молекул [75,76].…”
Section: заключениеunclassified